Alcohol substitution during one month of cannabis abstinence among non-treatment seeking youth - Schuster, Randi Melissa; Potter, Kevin; Lamberth, Erin; Rychik, Natali; Hareli, Maya; Allen, Sophia; Broos, Hannah C.; Mustoe, Audrey; Gilman, Jodi M.; Pachas, Gladys; Evins, A. Eden (Progress in neuro-psychopharmacology & biological psychiatry, 2021)
Cannabis and alcohol use are correlated behaviors among youth. It is not known whether discontinuation of cannabis use is associated with changes in alcohol use. This study assessed alcohol use in youth before, during, and after 4 weeks of paid cannabis abstinence. Healthy, non-treatment seeking, cannabis users (n = 160), aged 14–25 years, 84% of whom used alcohol in the last month, were enrolled for a 4-week study with a 2–4 week follow-up. Participants were randomly assigned to 4 weeks of either biochemically-verified cannabis abstinence achieved through a contingency management framework (CB-Abst) or monitoring with no abstinence requirement (CB-Mon). Participants were assessed at baseline and approximately 4, 6, 10, 17, 24, and 31 days after enrollment. A follow-up visit with no cannabis abstinence requirement for CB-Abst was conducted after 2–4 weeks. Sixty percent of individuals assigned to the CB-Abst condition increased in frequency and quantity of alcohol consumption during the 4-week period of incentivized cannabis abstinence. As a whole, CB-Abst increased by a mean of 0.6 drinking days and 0.2 drinks per day in the initial week of abstinence (p's < 0.006). There was no evidence for further increases in drinking frequency or quantity during the 30-day abstinence period (p's > 0.53). There was no change in drinking frequency or quantity during the 4-week monitoring or follow-up periods among CB-Mon. On average, 4 weeks of incentivized (i.e., paid) cannabis abstinence among non-treatment seeking youth was associated with increased frequency and amount of alcohol use in week 1 that was sustained over 4 weeks and resolved with resumption of cannabis use. However, there was notable variability in individual-level response, with 60% increasing in alcohol use and 23% actually decreasing in alcohol use during cannabis abstinence. Findings suggest that increased alcohol use during cannabis abstinence among youth merits further study to determine whether this behavior occurs among treatment seeking youth and its clinical significance. •Four weeks of cannabis abstinence among non-treatment seeking youth was associated with increased alcohol use.•Increases in alcohol use occurred in week 1, were sustained over 4 weeks, and resolved with resumption of cannabis use.•There was notable variability, with 60% increasingand 23% decreasing in alcohol use during cannabis abstinence.